2017
DOI: 10.1002/elps.201700192
|View full text |Cite
|
Sign up to set email alerts
|

Mutation rates in 21 autosomal short tandem repeat loci in a population from Goiás, Brazil

Abstract: The appearance of new mutations in polymorphic markers plays a central role in a range of genetic applications, including dating phylogenetic events, informing disease studies, and evaluating forensic evidence. The present study estimated the mutation rates of 21 autosomal STR loci in a population from Central Brazil. We studied 15 046 paternity cases from Goiás, Brazil from August 2012 to February 2015. We identified 262 mutations in the 21 loci. The loci that presented more mutations were FGA and D18S51, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Based on the number of meiosis per locus, the overall mutation rate determined in this study for the 15 forensic STR loci was 1.3 × 10 −3 (95% CI: 1.1–1.5 × 10 −3 ), which is a similar value to the findings of previous studies with Brazilian populations of the Southern and Southeastern regions , and with Polish and Southern Chinese Han populations, which ranged from 1,18 × 10 −3 to 1,39 × 10 −3 . The mutation rate calculated in this study is, however, slightly different from an earlier study including Southern, Southeastern and Central Brazilian populations (0.94 × 10 −3 ) and data published for the Northeastern region of the country (0.75 × 10 −3 ) , and much higher than the rate reported in a recent study analyzing a population from Central Brazil (0.21 × 10 −3 ) .…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indcontrasting
confidence: 99%
See 2 more Smart Citations
“…Based on the number of meiosis per locus, the overall mutation rate determined in this study for the 15 forensic STR loci was 1.3 × 10 −3 (95% CI: 1.1–1.5 × 10 −3 ), which is a similar value to the findings of previous studies with Brazilian populations of the Southern and Southeastern regions , and with Polish and Southern Chinese Han populations, which ranged from 1,18 × 10 −3 to 1,39 × 10 −3 . The mutation rate calculated in this study is, however, slightly different from an earlier study including Southern, Southeastern and Central Brazilian populations (0.94 × 10 −3 ) and data published for the Northeastern region of the country (0.75 × 10 −3 ) , and much higher than the rate reported in a recent study analyzing a population from Central Brazil (0.21 × 10 −3 ) .…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indcontrasting
confidence: 99%
“…We observed the highest STR mutation rates at loci vWA (2.8 × 10 −3 ), FGA and D18S51 (both with 2.7 × 10 −3 ), while loci TH01 and TPOX had no mutations. In previous studies performed in Southern and Central Brazil populations, vWA, FGA, and D18S51 were also the loci presenting the highest mutation rates, while TH01 and TPOX also presented very low mutation rates. Two other studies, one performed in a population from São Paulo and another one in Poland , reported the highest rates for vWA and FGA, with D12S391 and D5S818, being the third highest mutated loci, respectively.…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indmentioning
confidence: 68%
See 1 more Smart Citation
“…Sequences were analyzed and due to the repeat pattern of each sequence, it was possible to identify both mutations as paternal. The single step repeat gain/loss usually occurs due to slippage of the polymerase during replication, and this type of mutation is more likely to happen in paternal lineage cells due to the speed of cell divisions during spermatogenesis [14,15]. Mutations should be taken into account and the calculation of PI should be modified, for example using the models suggested by Brenner (http://dna-view.com/mudisc.htm) [11].…”
Section: Inconsistencies In Paternity Testingmentioning
confidence: 99%
“…Mutations should be taken into account and the calculation of PI should be modified, for example using the models suggested by Brenner (http://dna-view.com/mudisc.htm) [11]. However, it is important to distinguish between mutations and exclusions and this can be achieved by analyzing more loci [15]. In both [12] 15…”
Section: Inconsistencies In Paternity Testingmentioning
confidence: 99%